Diagnosis and Treatment of the Extraesophageal Manifestations of Gastroesophageal Reflux Disease. Issue 1 (January 2017) - Sidhwa, Feroze; Moore, Alessandra; Alligood, Elaine; Fisichella, Piero Marco
Abstract : Objective: To review the clinical presentation, diagnosis, and treatment options available for management of extraesophageal manifestations of gastroesophageal reflux disease (GERD) and to compare the most recent technological advances to the existing guidelines. Summary Background Data: Extraesophageal manifestations of GERD include cough, laryngopharyngeal reflux (LPR), and asthma. Recent advances in diagnostic modalities may have outpaced the existing diagnostic and therapeutic clinical guidelines. Methods: We searched the MEDLINE, Cochrane, and Embase databases for articles pertaining to the presentation, diagnosis, and treatment of extraesophageal manifestations of reflux, specifically cough due to reflux, LPR, and asthma due to reflux. Search terms applied to 3 thematic topics: diagnosis, medical treatment, and surgical treatment. We had searched the bibliographies of included studies, yielding a total of 271 articles for full review. We graded the level of evidence and classified recommendations by size of treatment effect, according to the guidelines from the American Heart Association Task Force on Practice Guidelines. Results: One hundred twenty-eight articles met criteria for analysis. Our findings show that the diagnosis of cough, LPR, or asthma due to gastroesophageal reflux is difficult, as no criterion standard test exits. Also, patients often present without heartburn or regurgitation typical of GERD. Combined multichannel intraluminal impedance, the pH (MII-pH) monitoring system, and the symptom association probability (SAP) test might distinguish extraesophageal manifestations of reflux from idiopathic chronic cough, laryngitis due to other causes, and atopic asthma. In addition, extraesophageal manifestations of reflux are most effectively diagnosed with a stepwise approach incorporating empiric treatment and antisecretory therapy, combined MII-pH monitoring, and surgical intervention in few selected cases. Conclusions: Recent studies demonstrate the potential diagnostic role of MII-pH monitoring. Surgical intervention provides resolution of extraesophageal symptoms less reliably than typical symptoms when the patient has GERD. Abstract : Supplemental Digital Content is available in the text